2015
DOI: 10.1002/syn.21840
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PDE2A, but not PDE9A, modulates presynaptic short‐term plasticity measured by paired‐pulse facilitation in the CA1 region of the hippocampus

Abstract: Phosphodiesterase (PDE) inhibitors are currently considered promising therapeutic targets for treatment of cognitive impairment in diseases such as Schizophrenia and Alzheimer's disease. Inhibitors of PDE2A and PDE9A have emerged as potential candidates shown to improve synaptic plasticity and memory function in animals. However, the functional relevance of their putative different localization in the neuron is not understood. Thus, this study aims at elucidating potential presynaptic effects of PDE2A inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…It is also noteworthy that the present study identified genome-wide significant evidence implicating three phosphodiesterase genes: PDE1C , PDE2A , and PDE4D . In particular, there is growing interest in PDE2A inhibitors as potential agents for cognitive enhancement (Trabanco et al 2016), and evidence suggests that these agents may enhance synaptic plasticity via presynaptic modulation of cAMP hydrolysis (Fernández-Fernández et al 2015). PDE4D inhibition is also under investigatation as a potential therapy for neurodegenerative disease (Ricciarelli et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that the present study identified genome-wide significant evidence implicating three phosphodiesterase genes: PDE1C , PDE2A , and PDE4D . In particular, there is growing interest in PDE2A inhibitors as potential agents for cognitive enhancement (Trabanco et al 2016), and evidence suggests that these agents may enhance synaptic plasticity via presynaptic modulation of cAMP hydrolysis (Fernández-Fernández et al 2015). PDE4D inhibition is also under investigatation as a potential therapy for neurodegenerative disease (Ricciarelli et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…At more advanced developmental stages, PDE2A expression has a widespread distribution in the central nervous system including the limbic system, olfactory cortex, amygdale, and hippocampus (Van Staveren et al ., ). Our study does not exclude roles of PDE2 in brain functions such as memory formation, inflammatory pain processing, and synaptic plasticity (Hu et al ., ; Kallenborn‐Gerhardt et al ., ; Redrobe et al ., ; Fernandez‐Fernandez et al ., ; Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…PDE2A is one of three isoforms of PDE2 and is highly expressed in limbic structures and basal ganglia of the brain and is concentrated in glutamate synapses [127]. Pre-clinical data has shown links to synaptic plasticity and cognition with PDE2A inhibitors having being investigated predominantly as treatments for schizophrenia and migraine, but they are also of interest in degenerative diseases [279][280][281]. 18 F-PF-05270430 is the only PDE2A-specific tracer, thus far, to be translated into man.…”
Section: Pde2amentioning
confidence: 99%